Spontaneous pneumothorax associated with COVID-19 - S Alaoui Rachidi; Y Motiaa (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Primary spontaneous pneumothorax is due to Spontaneous rupture of a subpleural bulla [1], this complication occured in 1% of COVID-19 patients [2]. We present a case of COVID-19 pneumonia associated with an isolated spontaneous pneumothorax without barotrauma.